2018
DOI: 10.1177/1756284818811508
|View full text |Cite
|
Sign up to set email alerts
|

Advances and challenges in the management of advanced fibrosis in nonalcoholic steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the most common type of chronic liver disease worldwide. From the spectrum of NAFLD, it is nonalcoholic steatohepatitis (NASH) that predominantly predisposes patients to higher risk for development of cirrhosis and hepatocellular carcinoma. There is growing evidence that the risk of progression to cirrhosis and hepatocellular carcinoma is not uniform among all patients with NASH. In fact, NASH patients with increasing numbers of metabolic diseases su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 97 publications
(122 reference statements)
0
17
0
4
Order By: Relevance
“…The authors are grateful to Ms Xiao Guo in the Joint Live Small Animal Imaging Laboratory of Fudan University Shanghai Medical College-PerkinElmer Company, for her technical support in the use of high resolution X-ray microCT scanning. Part of this work was presented in the 69th Annual Meeting of the American Association for the Study of Liver Diseases (AASLD), Nov. [8][9][10][11][12][13]2018, San Francisco, CA, USA, and published as an abstract in Hepatology 2018; 68:441A.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors are grateful to Ms Xiao Guo in the Joint Live Small Animal Imaging Laboratory of Fudan University Shanghai Medical College-PerkinElmer Company, for her technical support in the use of high resolution X-ray microCT scanning. Part of this work was presented in the 69th Annual Meeting of the American Association for the Study of Liver Diseases (AASLD), Nov. [8][9][10][11][12][13]2018, San Francisco, CA, USA, and published as an abstract in Hepatology 2018; 68:441A.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 99%
“…The lack of FDA‐approved medications for NASH treatment has resulted in the conduct of several clinical trials of potential therapeutics, such as the peroxisome proliferator‐activated receptor‐α/δ agonist Elafibranor, the farnesoid X receptor agonist obeticholic acid, the C‐C chemokine receptor‐2/5 antagonist Cenicriviroc, an apoptosis signal‐regulating kinase‐1 inhibitor Selonsertib, all of which are in phase III. Additionally thyroid receptor β agonists, VK2809 (AASLD 2018 Abstract LB‐4), MGL‐3196 (AASLD 2018 Abstract 14) or stearoyl‐CoA desaturase‐1 modulator, Aramchol (AASLD 2018 Abstract LB‐5) are in the pipeline . In addition to the improvement of NAFLD activity score (NAS), the resolution of hepatic fibrosis is one of major endpoints in these phase II and III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10,11) Recent studies indicate that patients with steatosis alone may develop steatohepatitis and progressive liver damage. (12,13) Several new drugs in development for NAFLD aim at decreasing the amount of fat in the liver (14,15) ; however, there are limited data comparing metabolic abnormalities and liver disease between patients with moderate to severe steatosis and those with mild steatosis. There are also very few studies correlating fat in the liver with fat deposition in other body compartments.…”
Section: Fat Accumulation Liver Fibrosis and Metabolic Abnormalitiementioning
confidence: 99%
“…Taking a holistic approach to patient care requires understanding the breadth by which this disease affects patients, from direct physical symptoms of the disease to its psychosocial impact [5][6][7][8]. Recognizing this reality of NAFLD is especially important as treatment options are currently limited to lifestyle modification aimed at weight loss, something that is often very challenging for patients both physically and emotionally to sustain [1,[9][10][11]. In addition to its negative effects on HRQL, recent studies have shown that NAFLD patients have a significantly reduced ability to perform daily activities as well as a much lower capacity for aerobic activity [12][13][14].…”
Section: Quality Of Life Burden Of Nafldmentioning
confidence: 99%